Penerapan Nilai-Nilai Etika Komunikasi Pada Mahasiswa Komunikasi Penyiaran Islam - Amelia putri daulay; Diana putri Auliyah Rahma; Najla Aqilah Halim; Nurfadila; Siti Asyaroh; Yetti Sumarni (CV. ITTC INDONESIA, 2024)
The application of ethical communication values ​​is essential in the context of communication education, especially for Islamic Communication and Broadcasting students. Students at the sixth semester level at UIN SU have passed the initial stage of learning communication theory and are now entering a phase where the application of these values ​​becomes crucial in daily communication practice. Data analysis was carried out inductively, where findings from interviews and observations were coded and analyzed to identify patterns, themes and variations in the application of communication ethical values. This approach provides a depth of understanding of how ethical communication values ​​are lived and implemented in the realities of student life. The selection of these qualitative techniques was guided by the aim of obtaining a holistic picture of how Islamic Broadcasting Communication students understand and apply ethical values ​​in their communication practices, as well as to provide a valuable contribution to the development of communication ethics education in the context of Islamic higher education.